Dynamics of tree layer composition, tree age and large diameter trees in Habitats Directive Annex I forest habitats in Estonia on the basis of monitoring data collected from 2010–2012 - Palo, Anneli; Gimbutas, Mark (Metsanduslikud uurimused, 2013)
The protection of late-succession forest habitats and continuous woodlands is the primary goal in Estonian forest nature conservation. Therefore ecological qualities of almost all forest stands in Estonian protected areas are described. Forest patches will be mapped and protected as Annex I forest habitats if they have enough structural and functional qualities. The member states of the European Union report in every six years about the conservation status of European Habitats Directive Annex I habitats. Changes in area as well as changes in habitat type’s structure and functions are also declared. In the present paper the dynamics in tree species composition, stand age and larger diameter trees of monitored Annex I forest habitats is analyzed. The mean age of stands is older than the Estonian mean value, but it is only slightly higher than the cutting age of the corresponding tree species. The mean diameter of larger living trees is in general larger than dead wood, which is indicative of the forest succession and historical low-intensive forest management. Currently, conservation activities support natural succession in forests that formerly were managed economically. Therefore, changes in the composition of tree layer species are to be expected. The dominance of spruce and the abundance of broad-leaved trees are increasing in non-managed forest habitats. In contrast, the proportion of pine, birch and aspen decreases significantly. In general the number of tree species in habitat patches will increase; thereby the dominance of certain species will decline. According to the Estonian interpretation of the forest types in the Manual of the Habitats Directive, some stands with changed main tree species will need to be reclassified. Therefore the area of some forest habitat types may increase in the future. On contrary the area and functional quality of some other habitat types may decrease.